Geld stinkt doch! Oder: Wie schmutziges Geld durch Geldwäsche auf saubere Konten gelangt - Altvater, Elmar (PROKLA. Zeitschrift für kritische Sozialwissenschaft, 2001)
Money is means of payment, it needs a legal form. Money resulting from illegal business lacks this legal shape, it needs “money laundering”. Methods of money laundering especially related to electronic banking and “shadow-banking” are discussed. The harmfulness of money laundering and is shown as well as the consequences for the social regime of time and space: only presence counts, instead of concrete territories abstract nodal points of networks come into play.